2006
DOI: 10.1177/0363546506288239
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic versus Open Shoulder Stabilization for Recurrent Anterior Instability

Abstract: Clinical outcomes after arthroscopic and open stabilization were comparable. Preoperative magnetic resonance arthrograms in shoulders with anterior instability allow an accurate diagnosis of intra-articular abnormality that correlates well with operative findings. Arthroscopic stabilization for recurrent anterior shoulder instability can be performed safely; the clinical outcomes are comparable to those after traditional open stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
182
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(200 citation statements)
references
References 35 publications
10
182
1
7
Order By: Relevance
“…A meta-analysis of 501 patients treated surgically for anterior shoulder instability using suture anchors (234 arthroscopic and 267 open) found similar rates of recurrent instability (6% versus 6.7%) and need for re-operation (4.7% and 6.6%) [49•]. Subjective evaluations show no significant difference between the two treatment methods, although loss of range of motion (notably external rotation) may be increased with open repairs [50][51][52]. Some have shown that patients treated with open techniques have a lower rate of recurrent shoulder dislocations or instability than those treated with arthroscopic techniques, with the caveat that almost half of those treated with open techniques had loss of external rotation (range 10-40°loss) [53].…”
Section: Arthroscopic Surgical Managementmentioning
confidence: 99%
“…A meta-analysis of 501 patients treated surgically for anterior shoulder instability using suture anchors (234 arthroscopic and 267 open) found similar rates of recurrent instability (6% versus 6.7%) and need for re-operation (4.7% and 6.6%) [49•]. Subjective evaluations show no significant difference between the two treatment methods, although loss of range of motion (notably external rotation) may be increased with open repairs [50][51][52]. Some have shown that patients treated with open techniques have a lower rate of recurrent shoulder dislocations or instability than those treated with arthroscopic techniques, with the caveat that almost half of those treated with open techniques had loss of external rotation (range 10-40°loss) [53].…”
Section: Arthroscopic Surgical Managementmentioning
confidence: 99%
“…Etkili fonksiyonel sonuçlar yanında artroskopik tedavi ile açık cerrahiye benzer sonuçlar elde etme hedefi ise, tedavide sütür çapaların kullanılmaya başlaması ile mümkün olmuştur (12)(13)(14). Hobby ve ark.…”
Section: Discussionunclassified
“…Open surgical techniques are also currently being used in treatment of first-time traumatic anterior shoulder dislocations. Many studies [29][30][31][32] have compared open surgical procedures with arthroscopic procedures for treatment of the same population as this review. However, these studies yielded different results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review 29) pooled 19 studies, and concluded that arthroscopic surgery was associated with significantly higher risk of recurrent instability compared to the open surgical procedure. Two studies 30,32) were prospective RCTs. One of them 30) demonstrated that both techniques yielded similar postoperative results, but recommended arthroscopic procedure because it can be performed safely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation